Hunger signs in plants - Faber, Ben (Revista Colombiana de Investigaciones Agroindustriales, 2015)
Soil, water and tissue analysis are all used to diagnose plant nutrition. This is often helpful and can confirm nutrient toxicities or deficiencies, but often the easiest and most direct technique is to look at the plant symptoms. All higher plants take on certain patterns on their leaves when there is a lack or overabundance of a certain nutrient. Para citar este artículo Faber, B. (2015). Hunger signs in plants. Rev. Colomb. Investig. Agroindustriales, 2(1), 69-72. DOI: http://dx.doi.org/10.23850/24220582.171